Effect of Different Rhizobium Strains on the Growth attributes of Black Gram (Journal of Life and Earth Science, 2011)
Effects of three different Rhizobium strains on the growth attributes of two black gram varieties (Vigna mungo L. Hepper) revealed differential varietal response due to inoculation with two types of Rhizobium strains. Treatment T5 showed higher values compared to the rest of the treatments. Different growth parameters such as RGR, LAR, RLGR, LAD, LAI, SLA and LWR indicated better results with the inoculation of nodule organism. Key words: Growth attributes; black gram; Vigna mungo; Rhizobium strains DOI: 10.3329/jles.v3i0.7438 J. Life Earth Sci., Vols. 3-4: 7-11, 2009